In vitro assessment of fungicides efficacy against fungal isolates causing Eucalyptus stem canker diseases in Ethiopia. (8th November 2022) - Admasu, Wendu; Sintayehu, Assefa; Gezahgne, Alemu
Abstract: Field surveys of E. camaldulensis diseases were conducted during 2019/20 and 2020/21 in Ethiopia. This species was found the most commonly planted in the surveyed fields and were showing stem canker diseases. Sampling was done from diseased stem and branches with clear symptoms. The morphological as well as PCR assay of the ITS1 and ITS2 loci were performed to identify the fungal pathogens. Lasiodiplodia theobromae and Didymella pinodella were the identified fungi. Four nationally licensed fungicides, Vitra (copper hydroxide), Ridomil gold (Metalaxyl-M + mancozeb), Liveshow (Pyraclostrobin + Epoxiconazole), and Sabozeb (Mancozeb) were evaluated for their in vitro efficacy against these fungi at concentrations of 500, 1000, 1500 and 2000 ppm for the management trial. Vitra and Liveshow were found to be the most effective fungicides at 2000 ppm for the control and treatment of Eucalyptus camaldulensis stem canker diseases. The findings from this research will provide foundation for future studies as this is the first report for the management of this Eucalyptus tree disease in Ethiopia.